Tyrosine kinase inhibitors as a first‐line treatment in patients with newly diagnosed chronic myeloid leukemia in chronic phase: A mixed‐treatment comparison. Issue 6 (28th October 2015) - Firwana, Belal; Sonbol, Mohamad Bassam; Diab, Maria; Raza, Shahzad; Hasan, Rim; Yousef, Ibrahim; Zarzour, Ahmad; Garipalli, Archana; Doll, Donald; Murad, M. Hassan; Al‐Kali, Aref
Abstract : Tyrosine kinase inhibitors (TKI) are the initial treatment for majority of newly diagnosed patients with chronic myelogenous leukemia (CML) in chronic phase (CP) and are associated with marked improvement in hematological, cytogenetic, molecular response and survival rates compared with other therapies. In this review, we summarize the evidence of TKI efficacy for patients with newly diagnosed CP‐CML. Six trials at low risk of bias evaluating TKIs as an initial treatment in adults with newly diagnosed CP‐CML and enrolling 2, 456 patients were included. Follow‐up times ranged from a median of 3 months to 5 years. Direct comparison showed statistically higher rates of major molecular response (MMR ≤ 0.1% IS ) achievement with second‐generation TKIs at 12 months which was sustained throughout treatment period. Bayesian mixed‐treatment comparison (MTC) analysis demonstrated superiority of both nilotinib and dasatinib over imatinib in terms of efficacy. Nilotinib was associated with higher deeper molecular responses (MR 4.5 ≤ 0.0032% IS ) at 60 months than dasatinib but no difference in MMR. The differences between nilotinib and dasatinib are likely clinically trivial. Among TKIs, nilotinib was found to have the best survival profile. Both nilotinib and dasatinib are associated with significantly better MMR compared to imatinib that is sustained over 60 months. This analysis shows that new‐generation TKIs are not only showing faster response but also maintaining a more potent one through longer follow‐up period. It is important to note out that MTC is not a substitute for well‐conducted RCTs investigating direct comparisons. Abstract : What's new? Tyrosine kinase inhibitors (TKI) are the initial treatment for the majority of patients newly diagnosed with chronic myelogenous leukemia (CML) in chronic phase. Current studies investigating TKIs for chronic CML however do not include head‐to‐head trials to compare second‐generation TKIs to each other. This study summarizes the evidence of TKI efficacy and indirectly compares second‐generation TKIs. Both nilotinib and dasatinib are associated with significantly better major molecular response compared to imatinib, which is sustained over 60 months. This analysis shows that new‐generation TKI are not only showing faster response, but also maintaining a more potent one through longer follow‐up periods.